2021
DOI: 10.26577/iam.2021.v2.i1.06
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Acs in Avicenna Balkhi Teaching Hospital in Afghanistan

Abstract: Background: One third of global deaths are caused by CVD, and the most common is IHD. Approximately 80% of IHD which is caused by atherosclerosis, with the remainder caused by non-atherosclerotic causes such as VHD, radiation, vasculitis, and other.Aim: To study the prevalence of ACS in Avicenna Balkhi Teaching Hospital. Methods: This is a retrospective cross sectional study, we collected data of 180 ACS patients from 01.01.2019 till 01.06.2019 in Avicenna Balkhi Teaching Hospital; data was evaluated on clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…7 After an ischemic occurrence, BNP levels peak in 14 and 40 hours.One of the most frequent reasons for admission to CCU is Non ST segment-elevation Myocardial infarction (NSTEMI), which could have a number of causes. 8 BNP levels were found to be more in stable angina than in unstable angina (UA) in another cross-sectional analysis. 9 Despite the fact that much research has been done on the significance of BNP in Heart Failure (HF), the novelty of the current study was to assess if BNP could predict mortality, heart failure, conservative management and cardiovascular events such as atrial fibrillation in patients diagnosed with ACS at RMI's CCU.…”
Section: Introductionmentioning
confidence: 87%
“…7 After an ischemic occurrence, BNP levels peak in 14 and 40 hours.One of the most frequent reasons for admission to CCU is Non ST segment-elevation Myocardial infarction (NSTEMI), which could have a number of causes. 8 BNP levels were found to be more in stable angina than in unstable angina (UA) in another cross-sectional analysis. 9 Despite the fact that much research has been done on the significance of BNP in Heart Failure (HF), the novelty of the current study was to assess if BNP could predict mortality, heart failure, conservative management and cardiovascular events such as atrial fibrillation in patients diagnosed with ACS at RMI's CCU.…”
Section: Introductionmentioning
confidence: 87%
“…This comes in agreement with our results. Other study showed a prevalence of HTN in STEMI patients of more than 50% (20) . In the study of Rallidis et al (21) , they found that Apo A was associated with higher likelihood of having premature ACS among 258 participants with elevated LDL-C levels.…”
Section: Discussionmentioning
confidence: 92%